PENGARUH DISIPLIN KERJA DAN PEMBERIAN REWARD TERHADAP KINERJA KARYAWAN - Diana; Usran Masahere (CV Edujavare Publishing, 2024)
Human Resource Management plays a crucial role in enhancing a company's competitive advantage, reducing costs, and increasing long-term profitability. Employee performance, as a critical factor in organizational success, is influenced by various factors such as discipline, motivation, job descriptions, commitment, rewards, leadership, competence, and organizational culture. This study examines the impact of work discipline and rewards on employee performance at PT Antilope Madju Puri Indah (AMPI), a property development company in Jakarta with 400 employees. Using a quantitative associative approach, data were collected from 80 randomly selected employees and analyzed with SPSS software. The results reveal that both work discipline and rewards have a significant positive effect on employee performance. Higher levels of discipline and well-structured reward systems contribute to greater employee motivation and performance. The study also indicates that the combined influence of these two factors significantly affects performance, with a large portion of the variance in employee outcomes explained by these variables. In conclusion, strengthening work discipline and implementing effective reward systems are key strategies for improving employee performance, which in turn supports the company’s overall growth and competitiveness in the property sector.